NANO-FE AND MWCNTS BASED NON-ENZYMATIC SENSOR FOR DETERMINATION OF GLUCOSE IN SERUUM - Wang, Jing; Wang, Yiting; Yu, Lei; Peng, Hui; Zhu, Jianzhong (LIFE: International Journal of Health and Life-Sciences, 2015)
The enzyme sensors based on glucose oxidase have been widely used for the detection of blood glucose. However, the activity of enzyme can be easily affected by temperature, pH, humidity and toxic chemical. Nanostructured metal-oxides have been extensively explored to develop nonenzymatic glucose sensors. An amperometric electrode based on multiwall carbon nanotubes (MWCNTs) and Fe nanoparticles has been successfully fabricated. The electrode exhibits the linear regression equation is: I = -0.1985 + 1.7499 CG (correlation coefficient is 0.9994). Linear response range: 0.2-20.0 mM, sensitivity: 1.75 a/am, the LOD was evaluated to be 0.03 mM according to IUPAC regulations (S/N = 3). Interference tests illustrated that 0.2 me of ascorbic acid and uric acid didn’t have effect on the determination of glucose. In the presence of 0.02 M chloride ion, the current signal of 0.2 mM glucose almost keeps unchanged at the sensor, revealing that this new sensor has high tolerance level to chloride ion. The sensor has been successfully applied to determine glucose in the serum samples and obtained consist results with conventional spectrometry.